KARAKTERISTIK USAHA KECIL DI INDONESIA Perencanaan Pemasaran Usaha Kecil Rumahan - Sidiq Permono Nugroho (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2010)
This paper describes briefly the rules which is closely related to the problems and obstacles in starting a home-based small businesses and explanations based on theories from several sources as a reference in running a small business home